1997
DOI: 10.1046/j.1365-2362.1997.1980737.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the angiotensin‐converting enzyme inhibitor enalapril on blood haematopoietic progenitors and Acetyl‐N‐Ser‐Asp‐Lys‐Pro concentrations

Abstract: Acetyl-N-Ser-Asp-Lys-Pro (AcSDKP) is a physiological inhibitor of the proliferation of haematopoietic stem cells. In 12 healthy volunteers treated with the angiotensin-converting enzyme (ACE) inhibitor enalapril (20 mg day-1 for 15 days), we studied plasma and urinary AcSDKP levels, the in vitro degradation of AcSDKP by plasma ACE and the numbers of circulating haematopoietic progenitors (granulocyte-monocytic colony forming unit: CFU-GM; burst forming unit-erythroid: BFU-E; and mixed colony forming unit: CFU-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…At the end of the experiment, the plasma Ac-SDKP level was Histological sections illustrating myocyte cross-sectional area, interstitial collagen deposition (green), and capillaries (yellow; because images were exposed under fluorescent light, red color given by rhodamine is not apparent) from sham group and 2K-1C rats treated with vehicle, Ac-SDKP at 400 g · kg doubled in rats given Ac-SDKP compared with untreated hypertensive 2K-1C rats, values similar to those found in patients on long-term enalapril (an ACEI) for 25 days (3.97Ϯ0.75 nmol/L), 28 normal rats given captopril for 28 days (3.51Ϯ0.87 nmol/L), 29 or irradiated mice given lisinopril (another ACEI) for 72 hours. 30 Higher doses (800 g · kg Ϫ1 · d…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…At the end of the experiment, the plasma Ac-SDKP level was Histological sections illustrating myocyte cross-sectional area, interstitial collagen deposition (green), and capillaries (yellow; because images were exposed under fluorescent light, red color given by rhodamine is not apparent) from sham group and 2K-1C rats treated with vehicle, Ac-SDKP at 400 g · kg doubled in rats given Ac-SDKP compared with untreated hypertensive 2K-1C rats, values similar to those found in patients on long-term enalapril (an ACEI) for 25 days (3.97Ϯ0.75 nmol/L), 28 normal rats given captopril for 28 days (3.51Ϯ0.87 nmol/L), 29 or irradiated mice given lisinopril (another ACEI) for 72 hours. 30 Higher doses (800 g · kg Ϫ1 · d…”
Section: Discussionmentioning
confidence: 52%
“…In fact, long-term ACE inhibition has been associated with (1) a significant reduction in cardiac collagen deposition in spontaneously hypertensive rats, 17 in rats with renovascular 33 or aldosterone-salt-induced hypertension, 34 or in hypertensive patients 35 and (2) a significant increase in plasma Ac-SDKP in patients, normal rats, or irradiated mice. 9,28,30 Long-term ACE inhibition in hypertension is associated with decreased collagen deposition, blood pressure, total peripheral resistance, and cardiac hypertrophy and improved cardiovascular function. However, these ACEI effects do not necessarily indicate whether reduced LV collagen deposition is due to hemodynamic changes, inhibition of conversion of Ang I to Ang II, increased tissue and/or circulating kinins, and/or increased Ac-SDKP plasma levels per se.…”
mentioning
confidence: 99%
“…3 Not only are all the components of the RAS detectable in bone marrow and marrow-derived circulating blood cells, but there is also considerable evidence that supports the involvement of Ang II in several haematological processes. [4][5][6][7] The actions of Ang II are primarily mediated through AT 1 -and AT 2 -receptors, both of which are seven-transmembrane G-protein coupled receptors that share approximately 34% homology. 8,9 The cell signalling and physiological effects associated with AT 1 receptor activation are currently the most thoroughly defined.…”
Section: Introductionmentioning
confidence: 99%
“…A significant decrease via enalapril was observed in erythroid burst-forming units (BFU-Es) and the granulocyte-monocytic colony forming unit (CFU-GM) while increasing the mixed colony forming unit (CFU-mixed). 20 In a study by Rodgers et al 21 , it was shown that AT1a receptors are present in human CD34+CD38-cells, CD34+CD38+ cells, lymphocytes and stromal cells. They also demonstrated that Ang II increases the proliferation of haematopoietic progenitor cells.…”
Section: Discussionmentioning
confidence: 98%